Cavity Design via Entrapment of Tetrapyrrole Macrocycles in Sol–Gel Matrices for Catalytic, Optical or Sensoring Functions - M.A. García-Sánchez; R.I.Y. Quiroz-Segoviano; F. Rojas; E.C. Menchaca-Campos; S.R. Tello–Solís; L. Munguía-Cortéz; L.A. Díaz-Alejo; E. Salas-Bañales (Adsorption Science & Technology, 2012)
The physicochemical and luminescent properties of tetrapyrrole macrocycles, such as the porphyrins (H 2 P) and phthalocyanines (H 2 Pc), were preserved by trapping or bonding these species in silica matrices. The method involved used hydroxy-aluminium tetrasulphophthalocyanine OH(Al)TSPc as a probe to find optimal conditions for the entrapment of tetrapyrrole molecules. This methodology made possible the trapping or fixing of macrocyclic species or their respective complexes in the interior of pores existing in monolithic, translucent, normal, or organo-modified silica xerogels. The average pore sizes ranged from 2.0 to 3.6 nm in these systems and depended on the structure, the nature of the cation in the complex and on the identity and position of the substituents at the periphery of the macrocyclic species. Under appropriate conditions, the tetrapyrrolic species can be trapped or bonded to the pore network in stable and monomeric form; however, the interactions with Si–OH groups on the pore walls inhibit the efficient displaying of its properties. To avoid this deleterious effect, some strategies are used, such as to place the macrocycle far from the pore walls through long bridges or by substituting Si–OH groups with alkyl or aryl species. Average pore diameters vary from 3.5 to 9.4 nm when long unions are established between the macrocycle and the pore walls or when more of one macrocyclic species are trapped inside each pore. The spectroscopic properties of the macrocycles trapped in these systems are similar to those displayed by the same species in solution. When phthalocyanines or porphyrins are trapped or bonded to the pore walls of organo-modified silica, the spectroscopic properties are better preserved and their intensities are a function of the chain length of the alkyl group present in the silica matrix. This last result suggests the possibility of tuning the pore size and polarity inside them by choosing the tetrapyrrole species that can be trapped or bonded; in this way, it is possible to create more efficient systems for catalytic, optical, sensoring and medical applications.